Epidemiological Patterns of Animal Bites in the Najafabad, Center of Iran (2012–2017) - Sanaz Amiri (Ubiquity Press, 2020)
Background: Animal bite due to the risk of rabies is a major public health problem. Rabies is of great importance because of fatalities and economic damage. Objective: This study was conducted to investigate the epidemiological patterns of animal bite in Najaf Abad during the years of 2012 to 2017. Methods: This is a cross-sectional study. All records (4,104) were registered in the registration offices of animal bites during the years of 2012 to 2017 at the rabies treatment centres of Najafabad by census method. Demographic characteristics, animal type and sometime clinical patterns of the wounded were examined. Results: The mean age of the injured was 31.28 ± 15.28 years. Of the 4,104 injured, 3648 (88%) were male and the rest of them were women. In terms of residential area, 3645 people (88%) were in urban areas and the rest were in rural areas in the place of occurrence of bites. Most cases of animal biting occurred in dogs (70.9%) and then cat (24.3%). The most affected part was 51% with shoulder and hand. In this study, the incidence of animal bites is estimated as 100,000 people per year in Najaf Abad in in 2012 it was 206.4, with an increasing trend to 212.9 in 2019 (P < 0.001). Conclusion: The results of the study showed that most cases of animal bites were related to dogs, urban areas and male sex variables. The incidence of animal bites was also increasing. Due to the importance of this disease and its financial losses, it is recommended that prevention methods should be used to control stray dogs, vaccination of domesticated dogs and to raise awareness of the people.